A Systems Approach to Government Management: An Analysis of the Department of Settlement and Infrastructure - Johny Urbanus Lesnussa; Montgomery Warbal (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
This study aims to analyze the government management process from the perspective of the organizing system, including division of labor, departmentalization, distribution of authority, and coordination in achieving efficiency and effectiveness at the Department of Settlements and Infrastructure of Ambon City. Using a descriptive qualitative approach, data were collected through literature review, observation, interviews, and documentation. The findings reveal that the division of labor is not fully aligned with main tasks and functions, departmentalization is relatively well implemented, while the distribution of authority and coordination remain weak, resulting in suboptimal integration and overall inefficiency and ineffectiveness in organizational performance.